Beliefs and Risk Awareness on Medications Among Pregnant Women Attending the Antenatal Care Unit in Ethiopia University Hospital. Overestimating the Risks Is Another Dread - Tefera, Yonas Getaye; Gebresillassie, Begashaw Melaku; Getnet Mersha, Amanual; Belachew, Sewunet Admasu (Frontiers in Public Health, 2020)
Background: Most studies on drug use during pregnancy were generally focused on potential teratogenicity effects. However, beliefs and risk awareness of medications can also influence the medication use and fetal well-being. Objective: This study aimed at assessing the risk awareness and beliefs towards medication use among pregnant women attending antenatal care unit in an Ethiopian university hospital. Method: A cross-sectional study was employed on pregnant women who were attending for antenatal care service at Gondar university referral hospital from March 15, 2016, to April 15, 2016. Pretested structured interview questionnaire adopted from the Beliefs about Medicines Questionnaire (BMQ) was used for data collection. Chi-square test and binary logistic regression used to identify possible predictors influencing the outcome variables. Result: Of the 423 women approached, 384 agreed to complete the questionnaire (90.8% response rate) and the mean age of the participants was 27.22 ± 5.5 years. More than two-thirds of the respondents had two to three (46.1%) and greater than three (25.8%) pregnancy histories. A third and nearly half (45.6%) of the respondents were on the first trimester and second trimester of their gestational age, respectively. The majority (70%) of pregnant women think all drugs are harmful if taken during pregnancy. Only a few (4.2%) of the participants do not mind to take drugs without professional advice. Most (90 %) of the respondents were not willing to take drugs without professional advice. Pregnant women who came from the rural areas had 25% less likelihood to self-medication with an adjusted odds ratio of 95% CI, 0.75 (0.37, 0.96). Conclusion: In this study, overestimating and exaggerated beliefs of medication risks during pregnancy is a concern though cautious drug use is necessary and warranted. Adequate counseling has to be provided by physicians, pharmacists, and other healthcare professionals to change the pregnant women conservative attitudes and misinformed beliefs of medication risk.